Eccentric needle motion effect on near-nozzle dynamics of diesel spray. (15th October 2017) - Huang, Weidi; Moon, Seoksu; Gao, Ya; Li, Zhilong; Wang, Jin
Highlights: Eccentric needle motions in varied conditions were studied. Oscillation in spray axial velocity was correlated to the eccentric needle motion. Mechanism of the needle eccentricity effect on spray dynamics was discussed. Abstract: The eccentric needle motion has been regarded as an important cause of in-nozzle flow disturbances and hole-to-hole spray variations of modern fuel injectors. However, the experimental investigations on this subject have rarely been reported due to great difficulties in the direct measurements of eccentric needle motion and the flow characteristics of individual holes in an injection nozzle. In this study, the axial and eccentric needle motion and the near-nozzle spray dynamics of 3-hole, 5-hole and 8-hole diesel injection nozzles were investigated in varied injection pressure conditions using an X-ray phase-contrast imaging technique. The eccentric needle motion and near-nozzle spray axial velocity showed temporal oscillations during the injection with different oscillation frequencies. The frequencies of these two oscillations were independent to the nozzle hole number and injection pressure. To discuss the mutual dependency of these two oscillations, the time traces of the spray axial velocity were measured for individual holes. The results showed that the oscillation phase, frequency and amplitude of the spray axial velocity were almost identical for all holes, which indicated that the sac pressure variation rather than hole-to-hole flow variation can be the primary cause of the spray axial velocity oscillation by the eccentric needle motion. The adequacy of this consideration was thoroughly discussed using a mass balance model in the nozzle sac that predicted the sac pressure variation during an injection event.